2019
DOI: 10.1038/s41598-019-45353-2
|View full text |Cite
|
Sign up to set email alerts
|

On measuring nanoparticle toxicity and clearance with Paramecium caudatum

Abstract: As the extent to which aquatic environments are polluted with nano-scale objects is becoming known, we are presented with an urgent need to study their effects on various forms of life and to clear and/or detoxify them. A range of methods exist to these ends, but a lack of inter-study comparability arising from an absence of experimental standardisation impedes progress. Here we present experiments that demonstrate measurement of orchestrated uptake and clearance of two environmentally-relevant nano- and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Similar to other aquatic species, Paramecium exhibited pronounced chemotaxis, and this is likely one of the behaviors they rely on to avoid hazards and pursue prey [ 50 ]. Numerous studies demonstrated the attraction and repulsion behavior of Paramecium in response to a set of defined chemical cues, strongly indicating the presence of specific chemoreceptors [ 25 , 51 , 52 ]. Glycerol is a commonly used reagent to disrupt the electrical properties and integrity of membranes while maintaining a functional contractile system in Paramecium [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other aquatic species, Paramecium exhibited pronounced chemotaxis, and this is likely one of the behaviors they rely on to avoid hazards and pursue prey [ 50 ]. Numerous studies demonstrated the attraction and repulsion behavior of Paramecium in response to a set of defined chemical cues, strongly indicating the presence of specific chemoreceptors [ 25 , 51 , 52 ]. Glycerol is a commonly used reagent to disrupt the electrical properties and integrity of membranes while maintaining a functional contractile system in Paramecium [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The growth of T. thermophila was inhibited when exposed to polystyrene nanoplastics of 20.8-24.1 nm diameter due to induced calcium homeostasis, consequently increasing mitochondrial permeability and the generation of reactive oxygen species (Wu et al, 2021). Paramecium caudatum ingested starchcoated multi-core magnetite nanoparticles of 200 nm diameter, which acted as a chemoattractant and internalized them within its food vacuoles (Mayne et al, 2019). Ingestion of non-nutritious particles can affect the feeding behavior of ciliates, as observed on a Paramecium, which effectively eliminated the cyanobacterium microcystis but with the ingestion rate drastically reduced when the ciliate was exposed to 0.1 mg/L ZnO nanoparticles (Zhang et al, 2022).…”
Section: Ingestion Of Microplastics and Nanoplastics By Ciliated Micr...mentioning
confidence: 99%
“…Paramecium (Ciliophora, Oligohymenophorea) is a unicellular protist with a broad, nearly global distribution in fresh and brackish water bodies. This ciliate is studied, among other things ( Karunanithi et al, 2019 ; Kelz and Mashour, 2019 ; Mayne et al, 2019 ; Soares et al, 2019 ; Arnaiz et al, 2020 ) for the abundance and diversity of its endosymbionts ( Floriano et al, 2018 ; Garushyants et al, 2018 ; Grosser et al, 2018 ; Potekhin et al, 2018 ; Sabaneyeva et al, 2018 ; Schrallhammer et al, 2018 ; Castelli et al, 2019a , b ; Fokin et al, 2019 ; Koehler et al, 2019 ; Lanzoni et al, 2019 ; Plotnikov et al, 2019 ). Host-symbiont interactions and their outcome have been studied for example using Holospora ( Lohse et al, 2006 ; Hori et al, 2008 ; Fokin and Görtz, 2009 ; Nidelet et al, 2009 ; Duncan et al, 2013 , 2018 ; Banerji et al, 2015 ; Castelli et al, 2015 ; Dusi et al, 2015 ; Garushyants et al, 2018 ; Grosser et al, 2018 ) Caedibacter ( Kusch et al, 2002 ; Dusi et al, 2014 ; Grosser et al, 2018 ; Schu and Schrallhammer, 2018 ; Koehler et al, 2019 ) and Preeria ( Bella et al, 2016 ; Potekhin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%